2004
DOI: 10.1021/jf034742y
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Seeds of Teff (Eragrostis teff), Grass-pea (Lathyrus sativus), and Their Mixtures:  Aspects of Nutrition and Food Safety

Abstract: Fermentation of pure teff (Eragrostis teff), pure grass-pea (Lathyrus sativus), and their mixtures, 9:1 and 8:2 (teff/grass-pea) has been done at two temperatures (room temperature and 35 degrees C) in duplicate using the strains of Lactobacillus plantarum, for bacterial fermentation, and Aspergillus oryzae and Rhizopus oligosporus in succession for solid-state fungal fermentation as inocula. In addition, the natural or spontaneous and back-slopping methods of bacterial fermentation have been done on the above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 15 publications
6
38
0
Order By: Relevance
“…The high numbers of LAB are assumed to be responsible for the relatively high lactic and acetic acid production and thereby outcompeting non-acid-tolerant species. The fall in pH below 4, reported from different Ethiopian injera fermentations (Baye et al, 2013;Yigzaw et al, 2004) was similarly observed in our model set-up.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The high numbers of LAB are assumed to be responsible for the relatively high lactic and acetic acid production and thereby outcompeting non-acid-tolerant species. The fall in pH below 4, reported from different Ethiopian injera fermentations (Baye et al, 2013;Yigzaw et al, 2004) was similarly observed in our model set-up.…”
Section: Discussionsupporting
confidence: 85%
“…Before the batter is finally poured onto a clay plate and baked, a so-called "absit" is prepared by boiling a portion of the batter with water and adding it back to the fermenting batter, ensuring the desired textural quality of the baked injera pancake. Due to the use of ersho, the pH drops rapidly (Yigzaw et al, 2004) and reaches values below pH 4 within hours (Baye et al, 2013;Stewart and Getachew, 1962). As would be expected with acidification, microbial analysis of tef-injera batter has reported lactic acid bacteria (LAB) to be the major fermentative microbes accompanied by yeast, Enterobacteriaceae and Bacillus spp., but the latter was detected to a lesser extent (Nigatu and Gashe, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The overall amino acid profile of teff can be regarded as well-balanced (Table 2). Yigzaw et al (2004) reported that spontaneous fermentation of teff caused decreases in threonine, valine, isoleucine, and lysine contents by 30, 8, 20 and 17 %, respectively. According to this research finding, amino acids such as leucine, phenylalanine, and histidine showed no significant change, whereas methionine was increased by 90 %.…”
Section: Amino Acid Compositionmentioning
confidence: 99%
“…According to this research finding, amino acids such as leucine, phenylalanine, and histidine showed no significant change, whereas methionine was increased by 90 %. Fermentation with Lactobacillus plantarum (lactic acid bacteria) caused decreases in threonine, isoleucine, lysine, and valine by 28, 14, 17, and 6 %, respectively (Yigzaw et al 2004). They found that fermentation with lactic acid bacteria increased the amounts of leucine (12 %) and methionine (110 %), whereas phenylalanine and histidine remained practically the same.…”
Section: Amino Acid Compositionmentioning
confidence: 99%
“…The results of the present study also indicated that bacterial fermentation improves the nutritive value of GPS [22]. Nutritionally, it is tasty and protein-rich [6], but the presence of a variety of anti-nutritional factors hinders its free nutritional utilization [5]. Tannin, phytic acid and β-ODAP could be significantly reduced in grass pea fermented with Bacillus sp.…”
Section: Resultsmentioning
confidence: 61%